Comparative analysis of three decades' experience in the management of pregnant women with epilepsy: a real-life scenario - Válóczy, Réka; Fekete, István; Horváth, László; Mészáros, Zsófia; Fekete, Klára (Frontiers in Neurology, 2023)
Introduction: People with epilepsy have to face many problems, including regular follow-ups, taking anti-seizure medications (ASM) and fear of seizures. Pregnant women with epilepsy (PWWE) is a special group, with even more challenges, being responsible for the foetus as well. Our aim was to evaluate the change in the frequency of pregnancies over the years and the possible role of newer type ASMs concerning this change, shift in medication use over three decades and their possible impact on the outcome of the observed pregnancies.Methods: Data were retrieved from the prospective Epilepsy Database of the Outpatient Clinic at our tertiary centre between 01.01.1992 and 31.12.2020. Groups were formed for comparison in time and depending on whether regular care, consultation was our task. Statistical analysis was carried out using Microsoft Office Excel 2021. Basic statistics and categorical variables were assessed using Pearson's χ 2 test with Yates' correction. Differences were considered significant if p<0.05. Odds ratio and 95% confidence intervals were calculated wherever needed.Results: Altogether, 181 pregnancies were studied, mostly after 2002. The regular follow-up group consisted of 101 patients, 44.5% of them presented in the first trimester. The majority of seizureseither generalised or focal to bilateral tonic-clonic seizure type (85.6%). Pregnancies ended in live births in 91.7%, which number increase gradually improved over time, while spontaneous abortion did not differ significantly in the time interval groups. Mostly monotherapy was given. PWWEs had higher chances for seizure-freedom in the regular-care group (I): OR=2.9 (2.15-3.65) p<0.0001. Shift toward newer-type ASMs was found by time passing. Levetiracetam and lamotrigine were more commonly used in the regular care group (I), than by those patients who were sent to a consultation only and not treated at our centre (OR=3.18 (2.49-3.87) p<0.0001.This is the first study in our region to evaluate experience in the treatment and outcome among PWWE. Having received reliable care and safer ASMs, the number of pregnancies grew among PWWEs. Data suggested that specialised centres' care offered cooperation with obstetricians is important. Moreover, professional care can also enable PWWEs to have uneventful pregnancies.